Pengaruh Model Pembelajaran Kooperatif Terpadu Membaca dan Menulis Terhadap Kemampuan Membaca Pemahaman Murid Kelas 5 SDN Tembok Dukuh IV/86 Surabaya - Isnaini, Della; Popiyanto, Yudha; Suprihatien, Suprihatien (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this research is to determine the effect of the Integrated Cooperative Learning Model for Reading and Writing on the reading comprehension abilities of 5th-grade students at SDN Tembok Dukuh IV/86 Surabaya. This type of research is quantitative with an experimental method used. The independent variable in this study is the Integrated Cooperative Learning Model for Reading and Writing, while the dependent variable is the reading comprehension ability of the 5th graders. The population in this study is all 5th-grade students at SDN Tembok Dukuh IV/86 Surabaya, totaling 54 students. The sample consists of class 5A with 27 students as the experimental class and class 5B with 27 students as the control class. Data collection is carried out through tests and documentation. The data is analyzed using the T-test to determine performance by comparing the average final test scores of the experimental and control groups. The results of the data analysis show that there is a significant improvement in students' reading comprehension abilities given treatment using the Integrated Cooperative Model of Reading and Writing compared to the control class. This is reinforced by the results of the t-test which indicate that the significance value obtained is 0.000 < 0.005. Therefore, it can be concluded that the integrated cooperative learning model has a significant impact on students' reading comprehension abilities